Recombined humanized endostatin (Endostar) combined with chemotherapy for advanced bone and soft tissue sarcomas in stage IV - Xing, Peipei (Oncotarget, 2016)
PURPOSE: This retrospective case-series study evaluated efficacy and safety of Endostar combined with chemotherapy in the treatment of advanced bone and soft tissue sarcomas in stage IV. MATERIALS AND METHODS: Forty-seven patients diagnosed with stage IV bone and soft tissue sarcomas and treated with chemotherapy in Tianjin Medical University Cancer Institute & Hospital were reviewed. Of these patients, 23 patients were treated with Endostar plus chemotherapy (designated as combined group), and 24 patients received only chemotherapy (designated as control group). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR) and clinical benefit response (CBR) were analyzed to find the difference between these two groups with the purpose to investigate the role of Endostar in metastatic sarcomas. RESULTS: Endostar combined with chemotherapy had significantly increased PFS. In the combined group and control groups, the median PFS (8.6 months versus 4.4 months) and the CBR (47.8% versus 16.7%) showed significant difference (P = 0.032), while the median overall survival (11.7 months versus 10.6 months, P = 0.658) and the ORR (17.4% versus 8.3%, P = 0.167) showed no significant difference. The common grade 3-4 side effects for both groups were myelosuppression and transient elevation of transaminases. CONCLUSION: Endostar combined with chemotherapy had significant activity to increase the PFS and improve CBR in patients with advanced sarcomas, with tolerable side effects.